G181(P) Prophylactic red cell and platelet transfusions in paediatric haemato-oncology patients: lessons from a UK single-centre retrospective audit. (25th October 2020) - Hanssen, LLP; Hildyard, C; Staples, S; King, AJ; Murphy, MF
Abstract : Aims: Transfusion of blood components carries significant risk. Adherence to national guidelines on transfusion thresholds standardises patient care and helps guide decision making. Such guidelines are currently less evidence-based in paediatric than adult practice. This audit aims to capture real-world practice in a tertiary centre paediatric haematology/oncology unit. Methods: Blood transfusions to inpatients over four months between October 2018 and January 2019 were retrospectively analysed. Transfusion details, pre- and post-transfusion haemoglobin and platelet counts, and patient characteristics were obtained from BloodTrack and the electronic patient record (EPR). Patients with haemoglobinopathies were excluded from this audit. Results: Red cell transfusions (n=121) were given to 38 inpatients and prophylactic platelet transfusions (n=127) were given to 21 inpatients. Underlying conditions recorded were ALL (n=14), AML (n=3), Burkitt lymphoma (n=2), aplastic anaemia (n=1), and various solid tumours (n=18). Red cell transfusions largely conformed to national guidelines, with 95% given to patients with a pre-transfusion haemoglobin below 80 g/l and a median haemoglobin of 72 g/l. Two units of red cells were given in 12% of transfusions. While 34% of prophylactic platelet transfusions were given to patients with a platelet count <10.10 9 /l, 38% were given to patients with a pre-transfusion platelet count of 20.10 9 /l or greater without a valid indication documented in EPR. Half of these were given to a single patient with CMV retinitis at risk of retinal haemorrhage. Recorded pre-procedure platelet transfusions were given before lumbar punctures, surgery, lung biopsy, and tunneled central-line insertions. 6% of these were given at pre-transfusion platelet counts of >50.10 9 /l, as local guidelines specified a threshold of <80.10 9 /l for central line placement. A small number of patients received the majority of red cell and platelet transfusions; 64% of red cell transfusion and 71% of platelet transfusions were given to six and four patients respectively. Conclusion: This single-centre study shows that national guidelines for red cell transfusions are largely followed in paediatric haemato-oncology patients. However, a small number of complex patients and divergent local guidelines were responsible for low adherence to national platelet transfusion guidelines. To improve local transfusion practice, training of junior staff and spread of guidelines within the department are undertaken, after which re-auditing in 12 months is planned.